Smart Blind Walking Stick - Shahrizan, Nur Atiqah; Sanudin, Rahmat (Evolution in Electrical and Electronic Engineering, 2021)
A white cane is a device that aids blind or visually impaired person during walking. The white cane helps the user monitor their surroundings for obstacles or direction marks and also aids others in identifying that the user is blind or visually handicapped and providing proper care. This study aims to design a smart blind walking stick for blind people, in which numerous research has been carried out in this area. They were addressed and compared with each other such as a smart walking stick for the blind integrated with the SOS navigation system This system is anticipated to help blind people to walk with ease independently. There are buzzers on the system to alert the user if there is an obstacle. The circuit of the smart blind walking stick design is created using Proteus. The theory of the circuit is based on the emitting ultrasonic sound waves by the ultrasonic sensor to measure the distance of a targeted obstacle. The results show that the sensor would alert the user when the obstacle is detected. In conclusion, the walking stick works as intended, which are alerting users when obstacles present and sending SMS in an emergency situation.